Implementation of Baby Massage for Baby's Weight Gain in Babies Age 2-6 Months: Pelaksanaan Pijat Bayi untuk Peningkatan Berat Badan Bayi pada Bayi Umur 2-6 Bulan - Eva Ratna Dewi; Ingka Kristina Pangaribuan; Eka Falentina Tarigan; Deby Cyntia Yun; Dewi Maya Sari; Wita Nancy Sinaga (Jurnal Pengabdian Bidan Nasuha, 2022)
Introduction: Infant and child growth is an important part of child health surveillance. Newborn weight at birth is an important marker of maternal and fetal health and nutrition. Those who survive are more likely to suffer from stunted growth and lower IQ. The purpose of this community service activity is to be able to empower parents in the implementation and participation in monitoring baby growth. Methods: This community service was carried out at the midwife's clinic, Deby Cyntia Yun. Respondents in this service as many as 10 people. The results of the service can be seen that there is an increase in baby weight after baby massage is carried out on babies 2-6 months. Monitoring of infant growth should be carried out on an ongoing basis to improve children's health, and it is hoped that a follow-up will be carried out by the Midwife Deby Cyntia Yun clinic with the findings of growth disorders in infants. It is hoped that this service can be used as a source of information for the Midwife Clinic Deby Cyntia Yun that there are "evidence based" results about one of the midwifery interventions that can be used to increase baby's weight through the provision of massage techniques, so that it becomes a guideline in providing professional care for babies, provide health education to the baby's mother for baby health care and prevent other baby health problems that can affect the baby's growth and development through baby massage techniques.